2012
DOI: 10.3126/ejdi.v11i0.6103
|View full text |Cite
|
Sign up to set email alerts
|

Corporate social responsibility: evidence from Nepalese financial service and manufacturing sectors

Abstract: This study, first, aims to trace the evolutionary path of definitions and perspectives on corporate social responsibility (CSR) particularly during the last fifty years or so and then examine the Nepalese financial service and manufacturing sector managers' strategic and moral views on CSR. Besides, it also seeks to measure the CSR performance of companies and examine the relationship between management views on CSR and actual CSR performance. The study finds that the trend on CSR thinking has moved from phila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…As a part of community related CSR, cash donations appear the most practiced one and scholarship programs in education sectors appear as the next important activity. Likewise, Chapagain (2010) found that both financial service and manufacturing sectors of Nepal have above-average involvement in most of the CSR aspects. However, both sectors have weak involvement in community aspect of CSR.…”
Section: Status Of Csr Practicesmentioning
confidence: 96%
See 1 more Smart Citation
“…As a part of community related CSR, cash donations appear the most practiced one and scholarship programs in education sectors appear as the next important activity. Likewise, Chapagain (2010) found that both financial service and manufacturing sectors of Nepal have above-average involvement in most of the CSR aspects. However, both sectors have weak involvement in community aspect of CSR.…”
Section: Status Of Csr Practicesmentioning
confidence: 96%
“…There are some studies (SAWTEE & ECCA, 2010;Chapagain, 2010;Adhikari, 2012;Ghising, 2013;Adhikari, Gautam & Chaudhari, 2016) regarding the status of CSR in the Nepalese context as well. SAWTEE and ECCA (2010) from the survey of 124 companies found that the top most priorities of Nepalese businesses are to fulfill the needs and expectations of customers and shareholders.…”
Section: Status Of Csr Practicesmentioning
confidence: 99%
“…According to Chapagain (2010), CSR practices emphasize more on social and environment aspects to improve company performance. The findings of this study show that CSR practices encourage companies to implement CSRP such as social obligations and environmental management.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Organization performs corporate social responsibility for the growth and development of the business Sanitation is the secondary function (Ashley, 2012). CSR is not considered as the expenditure for the organization, but as strategic resources that enhances the performance and competitiveness of the corporation' (Chapagain, 2010). Corporate social responsibility is not to solve the world's problem but the capable companies can improve the life of the people by creating sustainable development opportunity in the society where it operates it business (Kandel, 2018).…”
Section: Introductionmentioning
confidence: 99%